Elevation of biomarkers and long‐term outcome after percutaneous coronary intervention. (November 2014) - Slimani, Alisson; Hanet, Claude; Jamart, Jacques; Gabriel, Laurence; Guedes, Antoine; Dangoisse, Vincent; Galanti, Laurence M.; Schroeder, Erwin
Abstract Background/Objectives The impact of an elevation of cardiac biomarkers occurring after percutaneous coronary intervention (PCI) on long‐term outcome remains controversial. Most available data are based on observational registries using multivariable analysis. In this study, a case–control approach was used to assess separately the impact of post‐PCI elevation of CK‐MB on the short‐term in‐hospital outcome and on the long‐term outcome after hospital discharge. Methods Between 1 January 1996 and 31 December 2008, a postprocedural rise of CK‐MB was observed in 363 among 8346 consecutive PCI procedures (4·3%). The overall in‐hospital mortality for patients with or without CK‐MB elevation after PCI was 8·5% and 1·5%, respectively (P < 0·001). For 245 hospital survivors with CK‐MB elevation, we found 245 control cases matched for 9 relevant clinical parameters in our PCI database during the same period. The long‐term survival of these patients was assessed by KM estimates. Results Despite an increased in‐hospital mortality among patients with periprocedural elevation of CK‐MB, the long‐term outcome of patients who are discharged alive is independent of CK‐MB release, curves of overall survival and of survival free of recurrence of myocardial infarction being similar up to 10 years after hospital discharge. Conclusions In our population, the elevation of CK‐MB after PCI identified a high‐risk subgroup for in‐hospital mortality but had no impact on the long‐term prognosis, once the patient is discharged alive from the hospital.